Development and Increase of Competitiveness of The Organization - Kalandarovna, Adburakhmanova Gulnora; Qizi, Azlarova Mushtariybegim Abror (Bumi Publikasi Nusantara, 2023)
In today's rapidly evolving business landscape, the development and enhancement of competitiveness within organizations stand as paramount drivers of sustained success. The correlation between organizational development – encompassing structural, cultural, and technological advancements – and an increase in competitiveness is intricately interwoven. A holistic approach that merges strategy, innovation, and people-centric processes proves vital. Organizations investing in continuous learning, adaptive frameworks, and cutting-edge technology position themselves favorably against competitors by driving efficiency, fostering innovation, and retaining talent. Furthermore, the era of digital transformation underscores the necessity of agility and resilience, with businesses that adapt to market changes often outperforming their more stagnant counterparts. This analysis emphasizes that an organization's commitment to developmental pursuits is intrinsically tied to its competitive edge, ensuring longevity and relevance in an ever-shifting marketplace.